2006
DOI: 10.1021/jf051772n
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Stale-Beer-like Odorant in Extracts of Naturally Aged Beer

Abstract: For a long time, beer staling has been a prime concern in brewery research. Yet, to improve flavor stability, better knowledge of all chemicals involved is still needed. From our aroma extract dilu-tion analyses (AEDA) applied to naturally aged lager beers emerged an old-beer-like odorant at RICP-SIL 5 CB = 1532 and RIFFAP = 2809, with a FD value close to that of trans-2-nonenal (the well-known cardboard off-flavor found in aged beers). Specific phenol extraction, GC cold trapping, and mass spectrometry (elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…These highly flavour-active volatile phenols, like 4-vinylphenol (4-VP) which originates from p-coumaric acid and 4-vinylguaiacol (4-VG), the decarboxylation product of ferulic acid, formed during thermal treatment and by enzyme activity, have been reported to influence the aroma and stabilise pigments of fruit juices (Fallico, Lanza, Maccarone, Asmundo, & Rapisarda, 1996;Rein, Ollilainen, Vahermo, Yli-Kauhaluoma, & Heinonen, 2005) and red wines (Morata, Gómez-Cordovés, Calderón, & Suárez, 2006). Some of the 4-vinyl derivatives of hydroxycinnamic acids, 4-VG and 4-vinylsyringol (4-VS), the latter the decarboxylation product of sinapic acid, are inherent to the beer production process, where they are formed by specific enzymes during fermentation or by thermal decarboxylation (Callemien, Dasnoy, & Collin, 2006;Vanbeneden, Gils, Delvaux, & Delvaux, 2008). In addition, 4-vinyl derivatives are considered to contribute to the smokey aroma of cured meat products (Guillén & Ibargoitia, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These highly flavour-active volatile phenols, like 4-vinylphenol (4-VP) which originates from p-coumaric acid and 4-vinylguaiacol (4-VG), the decarboxylation product of ferulic acid, formed during thermal treatment and by enzyme activity, have been reported to influence the aroma and stabilise pigments of fruit juices (Fallico, Lanza, Maccarone, Asmundo, & Rapisarda, 1996;Rein, Ollilainen, Vahermo, Yli-Kauhaluoma, & Heinonen, 2005) and red wines (Morata, Gómez-Cordovés, Calderón, & Suárez, 2006). Some of the 4-vinyl derivatives of hydroxycinnamic acids, 4-VG and 4-vinylsyringol (4-VS), the latter the decarboxylation product of sinapic acid, are inherent to the beer production process, where they are formed by specific enzymes during fermentation or by thermal decarboxylation (Callemien, Dasnoy, & Collin, 2006;Vanbeneden, Gils, Delvaux, & Delvaux, 2008). In addition, 4-vinyl derivatives are considered to contribute to the smokey aroma of cured meat products (Guillén & Ibargoitia, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Later, Meilgaard, Reid, and Wyborski (1982) included vanillin in the reference standards for their beer flavour terminology system. Recently, it was shown that 4-vinylguaiacol contributes to the overall flavour of certain Belgian beer styles with a clove-like aroma (Vanbeneden et al, 2008) and that 4-vinylsyringol may play a role in aged beer flavour (Callemien, Dasnoy, & Collin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the chemistry behind the ageing process is extremely complex, as many constituents 1,8,10,12,20,25,34,35,52,[56][57][58] derived from the raw materials or formed during the production process, may contribute in one way or another to beer flavour stability (e.g. anti-oxidants such as polyphenols) or flavour instability (e.g.…”
Section: Introductionmentioning
confidence: 99%